The Challenges and Obstacles to Exclusive Breastfeeding to Muslim Families in an Islamic and Health Perspective - Salamuddin Salamuddin; Rani Suraya; Zahrani Nabilah; Faiza Adinda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Breastfeeding is very important for babies between 0-6 months. Islamic teachings recommend that a mother must breastfeed her children with the aim that the child will be healthy for the survival and development of the child in the future. The purpose of this study is to find out the factors that cause challenges and obstacles to exclusive breastfeeding in Muslim families in an Islamic and health perspective. This research is a further analysis of Indonesian Social Demographic and Health secondary data in 2017. This research is a quantitative study with a cross-sectional research design. This research was conducted in Indonesia, where secondary data analysis was carried out from January to March 2023. The population in this study were married women aged 15-49 years who had children aged 0-6 months. The sample of this study were 3,319 mothers aged 15-49 years. Data analysis was performed using bivariate analysis with the chi-square statistical test. The results showed that there was a significant relationship between residence status and exclusive breastfeeding (p-value=0.009), there was a significant relationship between husband/partner's education level and exclusive breastfeeding (p-value=0.010), there was significant relationship between mother's work and exclusive breastfeeding (p-value=<0.001), and there is a significant relationship between wealth index combined and exclusive breastfeeding (p-value=<0.001). It is suggested to health workers and ustadz to increase education about the importance of giving 0-6 months breast milk in the perspective of health and Islamic religious teachings and it is suggested to health workers and ustadz to increase husbands' understanding about exclusive breast milk to increase the coverage of exclusive breast milk for mothers breastfeeding and does not hinder breastfeeding mothers in giving exclusive breast milk. Keywords: Health, Islamic Perspective, Mother's Milk